2017
DOI: 10.1007/s00464-017-5538-5
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and inter-operator variability of small bowel length measurement at laparoscopy

Abstract: Small bowel length assessment during laparoscopy is inaccurate and associated with substantial variability. There is a need to develop a standardized laparoscopic technique for measuring small bowel length which is simple, reproducible, and easy to learn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The study of Gazer et al assessed the reliability of laparoscopic bowel length measurement in 14 surgeons using an in vivo porcine model. They found that measured lengths were 36% shorter than the actual length, concluding that the assessment during laparoscopy was inaccurate [13]. However, the measurements were not performed by bariatric surgeons, which may explain the different outcomes, as general surgeons perform laparoscopic small bowel measurements to a much lesser extent than bariatric surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Gazer et al assessed the reliability of laparoscopic bowel length measurement in 14 surgeons using an in vivo porcine model. They found that measured lengths were 36% shorter than the actual length, concluding that the assessment during laparoscopy was inaccurate [13]. However, the measurements were not performed by bariatric surgeons, which may explain the different outcomes, as general surgeons perform laparoscopic small bowel measurements to a much lesser extent than bariatric surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Ten experienced surgeons, each with > 1000 laparoscopic surgeries, were asked to measure various lengths of small bowel without the aid of a measuring tool. Measured small bowel lengths were significantly shorter than in reality and the extent of the measurement error correlated with the length of the measured small bowel segment [ 30 ]. In contrast, Homan et al described the use of a measuring tape, which makes their study results more reliable in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of the length of the human small bowel is not just an anatomic data point but is also important for avoiding short (8,10,11). The common feature of these studies is that they were all conducted within the last few years.…”
Section: Discussionmentioning
confidence: 99%